‘Obsolescence(s) de l’homme’ - Manola Antonioli (Recherches Germaniques)
The article proposes to carry out a comparative study of three literary and cinematographic dystopias, Brave New World (1932), 1984 (1949) and the three episodes of The Matrix (1999-2003), considered as archetypal figures of what, in terms of political philosophy, could be called biopower (Foucault), totalitarianism (Hannah Arendt) and an extreme form of control society theorised by Gilles Deleuze, without omitting the decisive influence of Baudrillard‘s thought and his theory of the simulacrum on the Wachowski brothers (now sisters) and the script of Matrix. The aim is to analyse the numerous resonances between these works and the ‚human, all too human‘ dimension of our present and the omnipresence of technological devices in our experience of ourselves and in our perception of the world.